Exploring economic and policy determinants of FDI. A panel data analysis - Varum, C. A. (2007)
During the past decades, the world economy has witnessed a dramatic surge in foreign direct investment. There is increasing competition among economies in attracting inflows of FDI. There has been renewed research interest in trying to detect what are the economic and political conditions that make a local economy an attractive destination for FDI inflows. Hence, in this paper we investigate macroeconomic and locational variables that may influence the level of FDI in a group of countries as a whole. In this paper we explore not only economic but also policy variables in terms of trade policy and regulation, and their effects on foreign direct investment. The evidence is captured by panel data analysis, which pools together 29 countries over the period 1990-2005. Overall our research shows that the distribution of FDI across countries is strongly determined by economic fundamentals and broad policies affecting foreign owned and domestic firms alike. Strategic and endurable horizontal policies, education and training in particular, can do much for the latter. There is scope for policies that are costless in the sense of having no immediate budgetary implications, namely the reduction of remaining impediments to trade.